2004
DOI: 10.1128/mcb.24.10.4546-4556.2004
|View full text |Cite
|
Sign up to set email alerts
|

E2F-Dependent Histone Acetylation and Recruitment of the Tip60 Acetyltransferase Complex to Chromatin in Late G1

Abstract: E2F proteins can either activate or repress transcription. Following mitogenic stimulation, repressive E2F4-p130-histone deacetylase complexes dissociate from, while activating species (E2F1, -2, and -3) associate with, target promoters. Histones H3 and H4 simultaneously become hyperacetylated, but it remains unclear whether this is a prerequisite or a consequence of E2F binding. Here, we show that activating E2F species are required for hyperacetylation of target chromatin in human cells. Overexpression of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
166
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(177 citation statements)
references
References 55 publications
10
166
0
1
Order By: Relevance
“…The p400/Tip60 ratio and cell proliferation L Mattera et al expression of genes essential for cell proliferation, such as E2F-dependent genes (Taubert et al, 2004)). Cancer cells would thus harbor a slightly decreased Tip60 function, high enough to be compatible with cell proliferation but not sufficient to promote stressinduced apoptosis (see the model in Figure 7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The p400/Tip60 ratio and cell proliferation L Mattera et al expression of genes essential for cell proliferation, such as E2F-dependent genes (Taubert et al, 2004)). Cancer cells would thus harbor a slightly decreased Tip60 function, high enough to be compatible with cell proliferation but not sufficient to promote stressinduced apoptosis (see the model in Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with its function in histone acetylation, Tip60 is mainly involved in transcriptional activation of specific genes (Gaughan et al, 2001;Berns et al, 2004;Legube et al, 2004). Transcriptional regulation of some genes, such as E2F or c-mycdependent genes, most likely involves the whole Tip60 complex (Frank et al, 2003;Taubert et al, 2004). However, it was recently shown that, on p21 promoter at least, Tip60 and p400 have antagonistic functions (Tyteca et al, 2006), with p400 functioning directly or indirectly as a repressor of Tip60 (meaning that p400 knockdown induces p21 expression in a Tip60-dependent way).…”
Section: Introductionmentioning
confidence: 89%
“…This mode of repression by Rb is in direct contrast to activation by E2F, which can bind to the histone acetylases (HATs) p300/CBP and P/CAF, making the DNA more accessible to transcription factors. RB/E2F-binding status, acetylation of E2F-dependent promoters and induction of transcription have been shown to be coordinated in a number of studies examining the proteins localized to the promoters of E2F-dependent genes at different stages of the cell cycle (Takahashi et al, 2000;Ferreira et al, 2001;Rayman et al, 2002;Caretti et al, 2003;Taubert et al, 2004). As compared to quiescent cells, in late G1 there is a loss of the pocket proteins and repressive E2Fs (E2F 4/p130), which are replaced by activating E2Fs.…”
Section: Mechanisms Of Transcriptional Controlmentioning
confidence: 99%
“…In this context, Pontin was identified as a component of different chromatin remodeling and modifying complexes including the Tip60, Ino80 and Uri complexes (for review see Gallant 2007). In addition, it has been shown that Pontin interacts with several transcription regulators like β-catenin, c-Myc and E2F1 and associates with the promoters targeted by these factors (Bauer et al 2000;Bauer et al 1998;Dugan et al 2002;Frank et al 2003;Taubert et al 2004;Wood et al 2000). Through its interaction with Hint1, Pontin modulates β-catenin mediated transcription in the canonical Wnt-signaling pathway and apoptosis (Weiske and Huber 2005;Weiske and Huber 2006).…”
Section: Introductionmentioning
confidence: 99%